PRINCIPLES OF DEVELOPING FOREIGN LANGUAGE PHONETIC AND PHONOLOGICAL COMPETENCY AS STRUCTURAL COMPONENT OF LINGUIST'S PROFESSIONAL COMPETENCE - Nina Goncharova; Tatyana Lomteva (Вестник Северо-Кавказского федерального университета, 2022)
The article postulates the importance of language students 'phonetic training for their future professional careers. The traditional concepts of teaching phonetics are analyzed and their disagreement with modern requirements to language specialists' expertise is revealed. The concept of foreign language phonetic and phonological competency as an inherent component of linguist's professional competence is introduced and an alternative conceptual model of its development is proposed. The article focuses on the description of general and specific didactic principles of creating the optimal psychological and pedagogical environment for the proposed model realization.